Pemanfaatan Game Edukasi dalam Pembelajaran SejarahMesir Kuno: Studi Kasus dan Analisis Persepsi Penggunaterhadap Game Archeologist: Ancient Egypt - Vany Mulyati Ornella Gunawan; Ganis Resmisari (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2025)
Learning methods are a crucial strategy in the learning process that helps students understand the material. Learning methods are related to students' learning motivation, especially in history, which is often considered boring by some students.Interactive and fun learning, such as educational games, can be an effective alternative to improve students' understanding and learning motivation. This study aims to evaluate the effectiveness of educational games as a medium for learning the history of Ancient Egypt, with a case study on the game Archaeologist: Ancient Egypt. This study uses a qualitative descriptive approach with data collection techniques through literature studies and questionnaires. The literature study was conducted through a SystematicLiterature Review (SRB) to identify key concepts regarding the effectiveness ofeducational games in learning history. Meanwhile, questionnaires were distributed to parents and children aged 7–12 years to obtain perception data regarding the use of the game Archaeologist: Ancient Egypt as a medium for learning the history of Ancient Egypt. Egypt. The questionnaire results showed that 87,3% of respondents agreed that educational games can improve students' understanding and learning motivation, especially in history lessons.